Introduction to genetic algorithms - Sivanandam, S. N. (Springer, 2007)
Designed to provide knowledge on the basic operational features and characteristics of Genetic Algorithms. This book also explores the different types of Genetic Algorithms available along with their importance. It contains basic concepts, several applications of Genetic Algorithms and solved Genetic Problems using MATLAB software and C/C++.